Management of phyllody in fennel by intercropping and insecticide use - K D Patel, A V Agalodiya, R K Jaiman, N R Patel, (Journal of Spices and Aromatic Crops, 2013)
Experiments were conducted during 2007–08 to 2010–11 at Centre for Research on Seed Spices, S.D. Agricultural University, Jagudan (Gujarat) for management of phyllody disease in fennel. Minimum incidence (9.80%) of phyllody with highest fennel equivalent yield (3035.28 kg ha-1) was observed in fennel inter cropped with green gram (1: 1). Maximum income Rs. 153632.60 ha-1 was observed in fennel + green gram intercropping. Minimum incidence of phyllody (9.19%) with highest yield (1947.17 kg ha-1) was recorded in seedling root dip in 0.04% Imidacloprid plus one spray of 0.005% Imidacloprid after one month of transplanting followed by seedling grown in 40 mesh nylon cloth net.